Prognostic Significance of Hypoalbuminemia in Transcatheter Aortic Valve Implantation Patients: A Systematic Review and Meta Analysis of Diagnostic Test Accuracy - Destino Huvi; Jessica Adrya; Nihal Sofyan; Daffa Rizqi Fauzi; Alan Dharmasaputra; Srigita Varsha; Putri Dhiya Prameswari Wiyono (Medicinus, 2026)
ckground: Calcific aortic stenosis is common in older adults, and TAVR has expanded treatment to patients with high comorbidity and frailty. Serum albumin is an inexpensive marker that reflects inflammation, nutrition, and physiologic reserve, but its prognostic performance in TAVR needs clearer quantification. Methods: We performed a PRISMA/PRISMA-DTA–guided systematic review and diagnostic test accuracy meta-analysis of studies evaluating pre-procedural hypoalbuminemia in adults undergoing TAVR/TAVI. PubMed, Embase, and Scopus were searched from inception to 18 January 2026. Hierarchical models were used to pool sensitivity and specificity for 30-day mortality, and a random-effects model pooled hazard ratios for time-to-event mortality. Risk of bias was assessed using PROBAST. Result: Ten studies met inclusion criteria. Definitions of hypoalbuminemia varied (most commonly <3.3–3.5 g/dL). For predicting 30-day mortality, pooled sensitivity was 47.7% (95% CI 35.5–59.9) and pooled specificity was 76.0% (95% CI 62.9–89.2), indicating better rule-in than rule-out performance. Across studies reporting time-to-event outcomes, hypoalbuminemia was associated with higher mortality (pooled HR 1.15, 95% CI 1.03–1.29). PROBAST ratings were generally low risk for participants, predictors, and outcomes, with some concerns in the analysis domain. Conclusions: Pre-procedural hypoalbuminemia is a practical risk marker in TAVR patients, showing moderate specificity for early mortality and a consistent association with worse survival, supporting its use in peri-procedural risk stratification.